Factors That Influence UMKM Taxpayer Compliance After Establishment of Government Regulation Number 23 Year 2018 (Empirical Study in Rokan Hulu Regency) - Nur hayati; Nof rianty (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2019)
From the amendment to this regulation, the thing that becomes the spotlight of taxpayers is by changing the final PPh rate from 1% to 0.5%, this policy aims to stimulate UMKM business and besides, the government also hopes that MSMEs can easily carry out their tax obligations and provide relief tax rates aimed at individual taxpayers and corporate taxpayers in the form of cooperatives, limited partnership, firms and limited liability companies that own and receive gross receipts do not exceed Rp. 4,800,000,000 in one year. The purpose of this study was to determine the effect of Tax Rates, Socialization and Understanding on the implementation of UMKM Taxpayer Compliance Post Government Regulation No. 23 of 2018 both partially and simultaneously.This type of research is causative research, with the population being MSME taxpayers registered as taxpayers in RokanHulu district as many as 135 UMKM taxpayers for micro scale. Data collection techniques using documentation and questionnaires.Data analysis techniques using multiple linear regression analysis, coefficient of determination and partial and simultaneous tests. The results of research for the tax rate partially affect the compliance of taxpayers with a significance of under 5%. This shows that whether or not the taxpayer adheres is influenced by the intention of the taxpayer himself in taking action to comply with tax obligations. Parsing socialization influences taxpayer compliance with significantly below 5%. This shows that the more socialization carried out by the tax authorities, the compliance of individual taxpayers will increase. Understanding has a partial effect on taxpayer compliance with significantly below 5%. This shows that increasing taxpayer knowledge provided by the government regarding Government Regulation No. 23 of 2018 to taxpayers, the understanding of taxes, especially taxes for UMKM will be even better